PENGARUH HARGA, TINGKAT PENDAPATAN DAN LITERASI KEUANGAN TERHADAP PERILAKU KONSUMTIF MAHASISWA UNIVERSITAS MUHADI SETIABUDI DALAM BERBELANJA ONLINE MELALUI PLATFORM SHOPEE (STUDI KASUS MAHASISWA FEB NON REGULAR) - Linnisa Prayitno, Belinda Orva; Harini, Dwi; Dewi Mulyani, Indah (Faculty of economcs Universitas Singaperbangsa Karawang, 2024)
This research aims to identify whether price, income level, and financial literacy influence the consumer behavior of Muhadi Setiabudi University students in shopping online via the Shopee platform (case study of FEB Non Regular students). This research uses quantitative methods with non-probability sampling and purposive sampling techniques. The population of this study was 322 students, but the sample obtained was 178 respondents using the Slovin formula. Data was collected through a questionnaire distributed using Google Form to UMUS FEB Non Regular students. The research results show that based on the t test, the significance of the price variable is 0.524 > 0.05 so that the first hypothesis is rejected; The significance of the income level variable is 0.000 <0.05 so that the second hypothesis is accepted; and the significance of the financial literacy variable is 0.000 <0.05 so that the third hypothesis is accepted. The f test shows a significance of 0.000 < 0.05, so the fourth hypothesis is accepted. It can be concluded that the price variable partially has a negative and insignificant effect on consumptive behavior, while the income level and financial literacy variables partially have a positive and significant effect on consumptive behavior. Simultaneously, the variables price, income level and financial literacy together have a positive effect.